Integrating ZnS microspheres with Bi2Se3 sponge ball structures to realize high energy density with good stability for supercapacitors - Syed Awais Ahmad; Muhammad Arif; Iftikhar Hussain; Yingkai Liu; Weibin Zhang; Ting Zhu (APL Materials)
The growing demand for renewable energy has ignited an interest in novel materials to improve the efficiency of energy storage. This study introduces a straightforward hydrothermal technique to synthesize the pristine ZnS, Bi2Se3, and their composite ZnS–Bi2Se3, which is intended as a high-performance electrode material for supercapacitors. We evaluate the as-synthesized materials for their structural, morphological, and electrochemical properties for a better understanding of the charge storage mechanisms. The ZnS–Bi2Se3 composite exhibits high electrochemical activity and chemical stability, owing to a high specific capacitance of 745 F g−1 at 1 A g−1. Furthermore, an asymmetric supercapacitor with the ZnS–Bi2Se3||activated carbon configuration delivers a remarkable energy density of 56.66 Wh kg−1 and a power density of 4990.90 W kg−1. Density functional theory calculations further elucidate these results, showing optimized work function, total density of states, and atomic structure, which enhance the composite’s electronic conductivity and charge transfer capabilities. Based on these findings, metal sulfide–selenide composites may be economically feasible choices for the high-performance electrochemical storage of energy.